FRACTIONAL INTEGRALS INVOLVING -FUNCTION AND THE GENERAL CLASS OF POLYNOMIALS - JAIN, MONIKA (International Journal of Mathematical Archive, 2018)
The object of the present paper is to study a number of new and useful fractional integrals involving a product of three general class of polynomials and the Aleph( - function with xk (xh + dh)–w as general arguments in view of both the operators introduced by Saigo in 1978.